Optimalisasi Lahan Sawah Tadah Hujan melalui Penyuluhan Budidaya Tanaman Sorgum di Gampong Blang Nibong, Aceh Utara - Khaidir; Handayani, Rd. Selvy; Yusuf N, Muhammad; Dewi, Elvira Sari; Usnawiyah; Rahman, Arief (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2026)
Rainfed rice fields in Gampong Blang Nibong, Aceh Utara, have low productivity due to rice monoculture and limited water access. This community service activity applied a Farmer Field School (FFS) approach with demonstration plots to enhance farmers’ knowledge and skills in sorghum cultivation. Hands-on practice on a 0.5-hectare plot and participatory training, involving 25 members of the Blang Nibong Farmers Group, resulted in an 84.5% knowledge increase, with 72% of participants interested in allocating land for sorghum. The approach promotes crop diversification, improves land productivity, and strengthens household economic resilience. Program sustainability is ensured through a sorghum development group, management of demonstration plots as seed gardens, and active collaboration with stakeholders. Results indicate that participatory FFS training effectively facilitates technology adoption in rainfed fields while raising farmers’ awareness of the importance of adaptive agronomic innovations.